Neuromuscular changes during a four-week individualized in-season strength-training program based on the dynamic strength index in youth basketball players: A quasi-experimental study - Casado-Martínez P; Romero-Moraleda B; González-García J (PLoS ONE, 2026)
The dynamic strength index (DSI) is commonly used as a neuromuscular profiling metric to inform individualized strength-training decisions; however, evidence describing short-term in-season changes in DSI and constituent neuromuscular variables in youth team-sport athletes remains limited. This quasi-experimental applied study quantified neuromuscular changes during a four-week individualized in-season strength-training program in 21 youth basketball players (age: 16.4 ± 1.3 years). Players were stratified into high (>0.57), neutral (0.45–0.57), or low (<0.45) baseline DSI tertiles to prioritize training emphasis (maximal strength, mixed, or ballistic/plyometric, respectively). Participants completed three individualized sessions per week alongside regular basketball training. Pre- and post-intervention measures included countermovement jump (CMJ) height and peak force, isometric squat (ISOBelt) peak force, and estimated one-repetition maximum (1RM) back squat. DSI was subsequently calculated from CMJ and ISOBelt peak force values. The high DSI tertile showed increases in ISOBelt peak force ( p = 0.004, d = 2.10) and estimated 1RM back squat ( p = 0.002, d = 1.84), accompanied by a reduction in DSI ( p < 0.001, d = −1.56), whereas CMJ outcomes showed no statistically significant changes across tertiles (all p > 0.05). The neutral tertile showed an increase in estimated 1RM back squat ( p = 0.002, d = 0.89), although no significant interaction effects were observed. During the competitive season, DSI-based profiling was associated with distinct within-tercile neuromuscular changes over four weeks; findings should be interpreted as observational outcomes within an applied in-season context and may assist practitioners in guiding individualized in-season strength-training prioritization.